Rapport sur la révolution hongroise . Report on the Hungarian Revolution - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. The French translation of the report transmitted by the Permanent Delegate to the Committee on the Hungarian revolution based on the information of the Foreign Office and the UK Residence in Budapest.